O impacto de contratos públicos na atuação de cooperativas de coleta seletiva: estudo de casos no interior de São Paulo - Correa, Anabella (2022)
The selective collection is important from the environmental, economic, and social perspectives. However, the autonomous agents, who informally work on this, have no aid, protection or visibility. Therefore, their grouping in associations or cooperatives is recommended. Some environmental regulations instituted in 2007, with the “Política Nacional de Resíduos Sólidos” (Federal Law 12.305/2010) as a legal landmark, have encouraged the hiring of these cooperatives by the public authorities, recognizing their important role in the solid waste management chain. There is a consensus that the existence of a public contract is favorable for the empowerment of cooperatives, but it may not be enough. Thus, this research aims to assess the impact and consequences of the existence of contractual instruments between public entities and waste picker organizations. A comparative case study considered municipalities with the same population in the country of São Paulo state. In addition to quantitative surveys of collection, sale, and municipal coverage. The objective is to know the current scenario of each case, and also to propose suggestions for policies or actions that help to strengthen cooperatives or that can improve their performance. Therefore, a selection of municipalities with same population size in the state of São Paulo were selected for a comparative case study. It consisted of documentary research in addition to contracts surveys and analysis of economic, social, environmental and governance aspects of the cooperatives. The results indicate that contracts, when well-planned, are important for the success of both the cooperative and selective collection. The existence of a cooperation agreement is still better than the absence of any formalized partnership with the government. Unfortunately, it still does not recognize these collectors as service providers, as established by solid waste legislation. In addition to the signing of contracts, the importance of support networks, the establishment of a waste management fee and the increase in reverse logistics partnerships with manufacturers and traders is pointed out, applying shared responsibility to all links in the chain.